THE FUTURE OF PLANT-BASED MEAT ALTERNATIVES: INNOVATIONS IN FOOD TECHNOLOGY (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article explores the future of plant-based meat alternatives and the role of food technology in driving innovation in this rapidly growing market. With increasing consumer demand for sustainable and healthy food options, plant-based meat alternatives have gained popularity as a viable alternative to traditional animal-based products. We examine the latest advancements in food technology, including novel ingredients, processing techniques, and product formulations that are shaping the future of plant-based meat alternatives. By leveraging these innovations, companies are able to create products that closely mimic the taste, texture, and nutritional profile of conventional meat, making them more appealing to a wider audience. The article also discusses the challenges and opportunities facing the plant-based meat industry and highlights key trends that are likely to shape its trajectory in the years to come.